Estudo de guias de onda com modificações estruturais para aplicações como sensor de índice de refração - Pinheiro Neto, Otavio de Paiva (Universidade Federal de São Carlos, 2024)
This final course project addressed integrated optical sensors exclusively based on waveguides, aiming to enhance the interaction of the guided mode's evanescent wave with the target analyte. Initially, structural modifications were introduced in the waveguides to optimize this interaction, inducing propagation losses and modulating the output power of the waveguide according to variations in the refractive index of the analyte. The interaction with the analyte was concentrated in a detection window, simplifying the complexity of optical sensors and reducing the high-resolution requirements of the equipment commonly used to measure resonant wavelength variations. Due to the complexity of the calculations involved, computational simulations were performed using the commercial software RSoft, specifically with the BeamPROP module, enabled by a partnership with the Research Laboratory in Devices (LPD) at the State University of Campinas (UNICAMP). The project also investigated the use of absorber materials, strategically positioned to modulate the interaction of the evanescent wave based on variations in the refractive index of the analyte. This method intensified the changes in the output power of the waveguide, facilitating the precise monitoring of refractive index variations. Finally, microfabrication processes were addressed to enable these optical sensors, culminating in the development of a fabrication roadmap and virtual lithographic masks. The results indicated the feasibility of developing highly sensitive and simpler-to-monitor sensors with potential for diverse applications, including the measurement of hemoglobin concentrations in human blood.
Study of waveguides with structural modifications for applications as refractive Index sensors
Keywords: Sensor de índice de refração; Guia de onda; Onda evanescente; ENGENHARIAS::ENGENHARIA ELETRICA::MATERIAIS ELETRICOS